Protein purification : principles, high resolution methods, and applications - Janson, Jan Christer Ryden, Lars (VCH, 1989)
A comprehensive presentation of all major techniques for protein separation and analysis. Aimed at both beginners and experienced workers in the field the text contains a mixture of theory, methodology and selected applications, covering chromatography and electrophoresis methods.